2007
DOI: 10.1038/nature05993
|View full text |Cite
|
Sign up to set email alerts
|

p53 regulates maternal reproduction through LIF

Abstract: Extensive studies have shown that p53 is important in tumour prevention. However, little is known about its normal physiological function. Here we show that p53 is important in reproduction, in a gender-specific manner. Significant decreases in embryonic implantation, pregnancy rate and litter size were observed in matings with p53-/- female mice but not with p53-/- male mice. The gene encoding leukaemia inhibitory factor (LIF), a cytokine critical for implantation, was identified as a p53-regulated gene that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
361
2
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(384 citation statements)
references
References 18 publications
8
361
2
8
Order By: Relevance
“…LIF is the cytokine produced and secreted by the endometrium, regulating implantation [6]. Sufficient uterine LIF protein is an essential condition for implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIF is the cytokine produced and secreted by the endometrium, regulating implantation [6]. Sufficient uterine LIF protein is an essential condition for implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of apoptosis and angiogenesis related genes have been associated with implantation failure [3]. Moreover, recent studies have demonstrated that p53 regulates female reproduction and blastocyst implantation through leukemia inhibitor factor (LIF) [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, leukaemia-inhibitory factor-a cytokine critical for embryo implantation-was identified as a p53-regulated gene (Hu et al, 2007). Moreover, p53 has been shown to induce as many as 40 genes that can somewhat, though not directly, have antiapoptotic effects (Janicke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…4 Mutated p53 is frequently found in human cancers. 5 and predisposes Li-Fraumeni syndrome patients to cancer.…”
Section: Introductionmentioning
confidence: 99%